2016
DOI: 10.3390/su8070658
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Drivers of Community Perceptions of Mining Projects through Effective Community Engagement

Abstract: Sustainable mining has received much attention in recent years as a consequence of the negative impacts of mining and public awareness. The aim of this paper is to provide mining companies guidance on improving the sustainability of their sites through effective community engagement based on recent advances in the literature. It begins with a review of the literature on sustainable development and its relationship to stakeholder engagement. It then uses the literature to determine the dominant factors that aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…While it is usually not difficult to identify regulators and other government stakeholders relevant to relinquishment of a mine, it can sometimes be difficult to determine who forms the 'community' relevant to the mine. In mining industry terms, a community is generally defined as the inhabitants of the immediate and surrounding areas who are affected by a company's activities (Wang et al 2016), but in practice it can sometimes be difficult to define the zone of influence. Further, this can change as the mining company approaches and then enters the closure and relinquishment phases.…”
Section: Who Are Your Relinquishment Stakeholders?mentioning
confidence: 99%
See 2 more Smart Citations
“…While it is usually not difficult to identify regulators and other government stakeholders relevant to relinquishment of a mine, it can sometimes be difficult to determine who forms the 'community' relevant to the mine. In mining industry terms, a community is generally defined as the inhabitants of the immediate and surrounding areas who are affected by a company's activities (Wang et al 2016), but in practice it can sometimes be difficult to define the zone of influence. Further, this can change as the mining company approaches and then enters the closure and relinquishment phases.…”
Section: Who Are Your Relinquishment Stakeholders?mentioning
confidence: 99%
“…When mining companies look for a collective response from a community in relation to plans for relinquishment, or attempt to gauge community acceptance or resistance to custodial transfer of a former mine, they often aim to engage with 'key stakeholders' and 'community representatives' as if the views of these individuals are representative of the wider community. While this approach has merit, it means that companies sometimes overlook the fact that a community's response is shaped by the choices and strategic interactions of individuals within the community, by private rather than public responses, and individual rather than collective actions (Wang et al 2016). On this basis, it is important that the company develops a sound understanding of the range of stakeholders interested in and/or affected by a relinquishment project and the roles played by these stakeholders (including whether they are decision-makers, influencers, observers etc.…”
Section: Who Are Your Relinquishment Stakeholders?mentioning
confidence: 99%
See 1 more Smart Citation
“…Mining corporations have adopted this governance approach in their social responsibility and sustainability agendas [14]. However, at the local level, corporations have encountered a major barrier when implementing this approach [15]. Corporate and government engagement with artisanal miners is very often challenging and therefore overlooked, or on the other hand being left out of conflict resolution processes in mining [13].…”
Section: Governance and Sustainable Community Developmentmentioning
confidence: 99%
“…Local stakeholders in isolation are not able to guarantee lasting community development valuable for local communities. Wang et al [15] identified existing limitations in a governance scenario. Many issues not related to violent conflicts are left out of peace processes, such as inequality and fair access to mineral resources.…”
Section: Governance and Sustainable Community Developmentmentioning
confidence: 99%